The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/chp.4750150408
|View full text |Cite
|
Sign up to set email alerts
|

Continuing education and health sciences libraries: Opportunities for collaboration

Abstract: Health care continuing education (CE) professionals and health sciences librarians have many common goals including ( I ) identibing information seeking behaviors of health professionals, ( 2 ) providing the information that hasDirectly or indirectly, health sciences librarians and continuing education (CE) professionals have long been working toward the same goal: ensuring that health professionals have the information and knowledge they need to deliver quality health care. Historically, CE and libraries coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In terms of session type, most included sources reported on librarians delivering a structured class or workshop session (n=90, 86%), but several unique examples described librarians developing and leading games [ 38 ], writing and presenting theatrical plays [ 39 ], and holding instructional exhibits [ 40 , 41 ]. The setting and formats of librarian teaching was fluid, as some sources described librarians visiting clinical teaching units to reach their audience [ 11 , 42 49 ], Some sources reported multiple session types and were coded as such.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of session type, most included sources reported on librarians delivering a structured class or workshop session (n=90, 86%), but several unique examples described librarians developing and leading games [ 38 ], writing and presenting theatrical plays [ 39 ], and holding instructional exhibits [ 40 , 41 ]. The setting and formats of librarian teaching was fluid, as some sources described librarians visiting clinical teaching units to reach their audience [ 11 , 42 49 ], Some sources reported multiple session types and were coded as such.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, authors of 59 included sources (56%) provided recommendations for future planning and teaching. Some suggested adding motivation to participate through formal accreditation: “CME credit also helped establish the relevance of information management to clinical practice” [ 37 ]; the value in leveraging partnerships: “Establishing a collaborative relationship with nurses and other health professionals will boost the visibility of librarians and the stature and professional impact in EB processes” [ 43 ]; and realizing the continuing education potential of existing resources: “Many health sciences libraries already have educational programs in place on various topics...CE professionals can tap into this existing pool of courses and request that they be tailored to fit specific audiences at CE conferences or exhibits” [ 40 ]. For the full list of captured suggestions, see Online Supplement Appendix 3 Table 5 .…”
Section: Resultsmentioning
confidence: 99%
“…4 This increasing emphasis on proactivity was echoed in McGowan's call for librarians to take a more active role in lifelong learning, 5 while collaboration was again discussed by Arnold and Humphries, who challenged librarians and CE educators to carry out ''research studies on information needs of health professionals to target specific areas for CE.'' 6 In 1977, Wender and colleagues at the University of Oklahoma conducted a major study to determine in part if there was a relationship between search request topics and areas of need for continuing medical education. 7,8 They concluded that, ''One may also consider the information requests the physician has made to his medical librarians to aid in determining his CME interests.''…”
Section: Introductionmentioning
confidence: 99%